Kimpul (Xanthosoma spp.) characterization based on morphological characteristic and isozymic analysis - NURMIYATI NURMIYATI; SUGIYARTO SUGIYARTO; SAJIDAN SAJIDAN (Nusantara Bioscience, 2009)
Abstract. Nurmiyati, Sugiyarto, Sajidan. 2009. Kimpul (Xanthosoma spp.) characterization based on morphological characteristic and isozymic analysis. Nusantara Bioscience 1: 138-145. This research is aimed: (i) to know the variety of kimpul (Xanthosoma spp.) based on morphological characteristics and isozymes analysis; (ii) to know the correlation between its genetic space based on morphological characteristics and its genetic resemblance based on isozymes-banding pattern. These research results were analyzed and described by descriptive qualitative methods. Morphological observation was carried out in sub-District of Galur, Lendah, and Girimulyo, Kulonprogo District, Yogyakarta. Morphological data of the kimpul plant was explored descriptively and then made dendrogram. Data of isozymic banding pattern were analyzed quantitatively based on the appearance of the band on the gel, and qualitatively based on the thickness of the band formed, and then made dendrogram. The correlation, between its genetic distance based on morphological characteristics and its genetic resemblance based on isozymes-banding pattern, were then analyzed grounded on coefficient correlation between product-moment and goodness of it criteria based on correlation. The results pointed out that morphologically, on eight observed samples which were consist of four different types (species), each Xanthosoma from different locations did not indicate obvious differences. Esterase was formed four different banding-patterns, Glutamate Oxaloacetate Transaminase indicated eight different banding-patterns, and Peroxidase indicated seven different banding-patterns. Correlation between morphological data and data from EST and GOT isozymic banding pattern was very good (0.967918 and 0.937113), While, the correlations between morphological data and POD isozymes were good (0.892721). goodness of it criteria based on correlation. The results pointed out that morphologically, on eight observed samples which were consist of four different types (species), each Xanthosoma from different locations did not indicate obvious differences. Esterase was formed four different banding- patterns, Glutamate Oxaloacetate Transaminase indicated eight different banding-patterns, and Peroxidase indicated seven different banding-patterns. Correlation between morphological data and data from EST and GOT isozymic banding pattern were very good (0.967918 and 0.937113), While, the orrelations between morphological data and POD isozymes were good (0.892721).